The grand strategy of the Roman Empire from the first century CE to the third - Luttwak, Edward 1942- (Johns Hopkins University Press, 2016)
"At the height of its power, the Roman Empire encompassed the entire Mediterranean basin, extending much beyond it from Britain to Mesopotamia, from the Rhine to the Black Sea. Rome prospered for centuries while successfully resisting attack, fending off everything from overnight robbery raids to full-scale invasion attempts by entire nations on the move. How were troops able to defend the Empire's vast territories from constant attacks? And how did they do so at such moderate cost that their treasury could pay for an immensity of highways, aqueducts, amphitheaters, city baths, and magnificent temples? In The Grand Strategy of the Roman Empire, seasoned defense analyst Edward N. Luttwak reveals how the Romans were able to combine military strength, diplomacy, and fortifications to effectively respond to changing threats. Rome's secret was not ceaseless fighting, but comprehensive strategies that unified force, diplomacy, and an immense infrastructure of roads, forts, walls, and barriers. Initially relying on client states to buffer attacks, Rome moved to a permanent frontier defense around 117 CE. Finally, as barbarians began to penetrate the empire, Rome filed large armies in a strategy of "defense-in-depth," allowing invaders to pierce Rome's borders. This updated edition has been extensively revised to incorporate recent scholarship and archeological findings. A new preface explores Roman imperial statecraft. This illuminating book remains essential to both ancient historians and students of modern strategy"...